PERANAN ADAPTIVE ITERATIVE DOSE REDUCTION 3D (AIDR 3D) DALAM MENINGKATKAN KUALITAS CITRA MSCT ABDOMEN - Ainiyah , Nur; Wijokongko , Sigit; Sulaksono , Nanang (JRI (Jurnal Radiografer Indonesia), 2021)
Background: Abdominal MSCT has better sensitivity and specificity, however its radiation exposure is high. Adaptive Iterative Dose Reduction (AIDR) 3D is an iterative reconstruction technology on Toshiba which produces a better image quality by reducing noise and streak artifacts in low dose. Based on author’s observation, abdominal MSCT performed at the hospital uses a standard routine abdominal MSCT protocol without adjusting the level of AIDR 3D. AIDR 3D has several strength level allowing an optimal image quality. This study was aimed to explain the role of AIDR 3D in improving the image quality and radiation dose of abdominal MSCT. Methods: This research method is descriptive with the literature study approach, by collecting articles from ProQuest, Google Scholar, PubMed, SpringerLink, and ScienceDirect about the role of AIDR 3D on abdominal MSCT published 2013-2020. The articles were selected according to the inclusion criteria. So there were 4 relevant journals which were then analyzed by making a journal summary, evaluating, giving opinions so that conclusions and suggestions can be drawn. Result: The results showed that AIDR 3D can improve the image quality of abdominal MSCT by reducing noise, artifacts and increasing CNR, SNR, image sharpness. Noise reduction and CNR increase, the most prominent SNR is found in AIDR 3D Strong, followed by Standard and Mild. AIDR 3D can reduce radiation doses better without reducing image quality Conclusion: AIDR 3D can improve image quality on abdominal MSCT and the use of integrated AIDR 3D SUREExposore 3D can reduce radiation doses better without reducing image quality. Reduction of radiation dose between 23% to 76%.